Signals of gastroesophageal reflux disease caused by incretin-based drugs: a disproportionality analysis using the Japanese adverse drug event report database - Yoshihiro Noguchi; Hayato Katsuno; Anri Ueno; Manami Otsubo; Aki Yoshida; Yuta Kanematsu; Ikuto Sugita; Hiroki Esaki; Tomoya Tachi; Teruo Tsuchiya; Hitomi Teramachi (BMC, 2018)
Abstract Background Incretin-based drugs are important in the treatment of type 2 diabetes. However, among the incretin-based drugs, glucagon-like peptide-1 receptor agonists (GLP-1-RAs) have been reported to cause gastroesophageal reflux disease (GERD)-like symptoms making it difficult to continue treatment. Therefore, with the aim of clarifying the relationship between incretin-based drugs and GERD-like symptoms, we conducted a pharmacoepidemiological study using the Japanese adverse drug event report database (JADER). Methods Dipeptidyl peptidase-4 inhibitors (DPP-4-Is) and GLP-1-RAs were set as the incretin-based target drugs. The reporting odds ratio (ROR) and the information component (IC) was used for the detection of quantitative signals. Furthermore, we also compared the time to onset of GERD-like symptoms by log-rank test. Results GERD-like symptoms were reported in 36 GLP-1-RAs cases (ROR: 5.61, 95% confidence interval (95% CI): 3.95-7.96 and IC: 2.17, 95% CI: 1.66-2.67) and GLP-1-RAs were detected in the signal. In contrast, DPP-4-Is were not detected in the signal. There was no sex difference with regard to the expression time of GERD-like symptoms by GLP-1-RAs (log-rank test, p = 0.5381). However, the expression time of GERD-like symptoms from GLP-1-RAs was shorter in patients older than 70 years of age than that in those younger than 70 years of age (log-rank test, p < 0.0001). Conclusions The administration of GLP-1-RA had a higher incidence of GERD-like symptoms earlier than the administration of DPP-4-Is. In this study, although we think that further investigation is necessary, and suggest that patients older than 70 years of age who have been administered GLP-1-RAs need earlier attention to address GERD-like symptoms than younger patients.